PCR detection, denaturing gradient gel electrophoresis (DGGE) fingerprinting and identification of the microbial consortium in different types of UASB granules - Keyser, Maricel (Stellenbosch: University of Stellenbosch, 2008)
Thesis (PhD (Food Science))--University of Stellenbosch, 2006.